2019
DOI: 10.1126/scitranslmed.aat3005
|View full text |Cite
|
Sign up to set email alerts
|

A farnesyltransferase inhibitor activates lysosomes and reduces tau pathology in mice with tauopathy

Abstract: Tau inclusions are a shared feature of many neurodegenerative diseases, among them frontotemporal dementia caused by tau mutations. Treatment approaches for these conditions include targeting posttranslational modifications of tau proteins, maintaining a steady-state amount of tau, and preventing its tendency to aggregate. We discovered a new regulatory pathway for tau degradation that operates through the farnesylated protein, Rhes, a GTPase in the Ras family. Here, we show that treatment with the farnesyltra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
88
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(98 citation statements)
references
References 65 publications
10
88
0
Order By: Relevance
“…[ 94–96 ] Rhes also plays a critical role in mutant tau‐mediated toxicity. [ 97 ] In addition, a rare, highly conserved de novo mutation (R57H) in Rhes was detected in twins diagnosed on the autism spectrum. [ 98 ] These studies illustrate significant and multifarious roles of Rhes in neuronal functions and neurological diseases.…”
Section: Rhes a Striatal‐enriched Brain Protein Induces Tnt‐like Prmentioning
confidence: 99%
“…[ 94–96 ] Rhes also plays a critical role in mutant tau‐mediated toxicity. [ 97 ] In addition, a rare, highly conserved de novo mutation (R57H) in Rhes was detected in twins diagnosed on the autism spectrum. [ 98 ] These studies illustrate significant and multifarious roles of Rhes in neuronal functions and neurological diseases.…”
Section: Rhes a Striatal‐enriched Brain Protein Induces Tnt‐like Prmentioning
confidence: 99%
“…Similar to previous studies, high-content microscopy was performed as reported by Hernandez et al 41 . Cells plated in glass-bottom 96-well plates were treated for the indicated times and, after fixation with 4% paraformaldehyde, images were acquired using a high-content microscope (Operetta, Perkin-Elmer).…”
Section: Methodsmentioning
confidence: 69%
“…4a). Next, we directly analyzed the effect of DSF in macroautophagy, the best characterized type of autophagy, using high-content microscopy in cells expressing a tandem mCherry-GFP-LC3 reporter 41 (Fig. 4b-d).…”
Section: Dsf Activates Cellular Autophagymentioning
confidence: 99%
See 1 more Smart Citation
“…NEK6 phosphorylates p70-S6 56 , a key player in hyperphosphorylation of Tau 57,58 that leads to microtubule disruption and deposition of Tau tangles. It was found to be relevant to the progression of AD and proposed as an early diagnostic biomarker 59,60 NEK9 was found to be differentially expressed in a tauopathy mouse model 61 .…”
Section: Polypharmacology Analysis Reveals Additional Mechanisms Thatmentioning
confidence: 99%